QUICK RESPONSE CODES IN IMPROVING STUDENTS’ VOCABULARY MASTERY - Sri Yuliyanti (Ma'soem University, 2021)
This study was aimed to investigate whether the implementation of Quick Response Codes is useful for the students in improving their English vocabulary. This study employed a Classroom Action Research (CAR) design in which the researcher worked collaboratively with an observer in the class. The CAR consisted of two cycles with the steps of planning, acting, observing and reflecting in each cycle. The data were gathered through several procedures, i.e. observation, interview, and tests. The result of this study showed that there was an increase in the students’ fulfillment of minimum mastery criterion from 0% before the treatment to 14.28 % after cycle 1 and 77.14% after cycle 2. Accordingly, the criterion of success was achieved. The results of observation revealed that the students actively participated in the learning process by using the Quick Response Codes in the vocabulary learning and it supported their engagement in the class.